Injury Severity among Young Drivers: A combination of Parametric and Non-parametric Analysis - Rusdi bin Rusli (LPPM NAROTAMA UNIVERSITY, Indonesia, 2020)
Young drivers among the group recorded highest fatalities index in road traffic crashes. The objective of this study was to identify factors affecting injury severity of young drivers using 5-years crash data (2008-2012) in Sabah, Malaysia. This study used a combination of parametric and non-parametric analysis to allows the specification of nonlinearities and interactions in addition to main effects. The results indicate that crashes on nighttime, federal roads and involved with a single-vehicle are positively associated with injury among young drivers. Interestingly, municipal roads, female drivers, crashes on the roundabout and T/Y junction are less likely to involve injury. A higher-order interaction suggests that not-at-fault young drivers involved with out-of-control or hit the object are more likely to be severe. On the other hand, young passenger car drivers involved in overturn and sideswipe collisions are negatively associated with the injury. It was also found that young drivers with driving too close behaviour are less likely to injure when involved in rear-end collisions for passenger car and four-wheel drive. Findings of this study will help relate authorities to design well-targeted restrictive measures in reducing the severity level of young drivers in traffic crashes.